Prevalence and whole-genome sequence analysis of Campylobacter spp. strains isolated from wild deer and boar in Japan - Morita, Satoshi; Sato, Shingo; Maruyama, Soichi; Miyagawa, Asuka; Nakamura, Kiriko; Nakamura, Mizuki; Asakura, Hiroshi; Sugiyama, Hiromu; Takai, Shinji; Maeda, Ken; Kabeya, Hidenori (Comparative immunology, microbiology and infectious diseases, 2022)
As a part of risk analysis for consumption of meat from wild animals, the prevalence of Campylobacter spp. in wild deer and boar in Japan was investigated. C. hyointestinalis subsp. hyointestinalis (C. hyointestinalis) was isolated from 2.8% (7/253) of the wild deer and 22.1% (71/321) of the wild boar examined. All 23 wild deer isolates and 141 (72.7%) wild boar isolates carried both chcdt-I and chcdt-II genes. The remaining 53 (27.3%) wild boar isolates had only the chcdt-II gene. By whole-genome sequence analysis, we detected 38–40 virulence- and survival-associated genes (motility, chemotactic, adhesion, invasion, toxin, glycosylation, iron uptake, drug resistance, and stress response), which had been identified in C. jejuni and C. coli. In conclusion, our study highlights C. hyointestinalis as a possible cause of food-borne disease in humans and emphasizes the importance of food hygiene in the processing of wild meats for human consumption. •Campylobacter hyointestinalis was more prevalent in wild boar (22.1%) than in deer (2.8%).•Whole genome sequencing detected 40 pathogenicity-related genes in the strains.•C. jejuni and C. coli were not isolated from any wild animals.•C. hyointestinalis should be reconsidered as a risk when consuming wild game meats.